2010
DOI: 10.1111/j.1742-7924.2010.00156.x
|View full text |Cite
|
Sign up to set email alerts
|

Health promotion behaviors of residents with hypertension in Iwate, Japan and North Carolina, USA

Abstract: Aim: The aim of this study was to compare the health promotion practises of rural residents in northern Japan (n = 212) to those in south-eastern North Carolina, USA (n = 105), using the Health Promotion Lifestyle II (HPLP) scale. Methods: A comparative and descriptive design examined the relationships between health-related behaviors and demographic and physiological variables, and compared cross-cultural patterns. Results: The Japanese participants scored significantly higher on the total HPLP II score, as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
1
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 52 publications
3
15
1
2
Order By: Relevance
“…However, other studies have found women with higher scores for health responsibility and interpersonal support than men, 31 with most studies on the subject showing gender as predictive of HPBs, because female gender was positively associated with these behaviors. 6,22,29 There was no association found between smoking and HPBs in this study. However, most research has indicated that non-smokers tend to engage in better health behaviors and have higher scores in health behaviors than smokers.…”
Section: Discussioncontrasting
confidence: 61%
See 3 more Smart Citations
“…However, other studies have found women with higher scores for health responsibility and interpersonal support than men, 31 with most studies on the subject showing gender as predictive of HPBs, because female gender was positively associated with these behaviors. 6,22,29 There was no association found between smoking and HPBs in this study. However, most research has indicated that non-smokers tend to engage in better health behaviors and have higher scores in health behaviors than smokers.…”
Section: Discussioncontrasting
confidence: 61%
“…There was no correlation between gender and HPBs in this study. However, other studies have found women with higher scores for health responsibility and interpersonal support than men, with most studies on the subject showing gender as predictive of HPBs, because female gender was positively associated with these behaviors …”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…One of these articles (Kemppainen et al [32]) reported data from two independent samples (USA and Japan samples), and therefore, we analyzed a total of 33 studies. Main characteristics of selected studies are reported in Table 1.…”
Section: Descriptive Characteristics Of Studies Included In the Meta-mentioning
confidence: 99%